Democracy, autocracy and the news: the impact of regime type on media freedom - Stier, Sebastian (Democratization, 2015)
Mass media is critical for the functioning of every contemporary political system. Thus, we can expect a variation in media freedom depending on the type of government since political regimes differ with regard to the political, legal and economic framework in which news coverage operates. This article investigates the effects of regime types, namely democracy and autocratic subtypes, on media freedom. It is argued that regime legitimation and governance are the driving forces behind diverging media policies in autocracies. From this theory, hypotheses regarding media freedom and regime type are derived and tested empirically, relying on statistical analyses that cover 149 countries over a period from 1993 to 2010. The empirical results demonstrate that democracies lead to significantly higher levels of media freedom than autocracies, with other things being equal. Within the autocratic spectrum, electoral autocracies, monarchies and military regimes have the freest media, whereas the most illiberal media can be found in communist ideocracies, where the ruling party holds a communication monopoly. Media freedom in personalist and non-ideological one-party regimes is on an intermediate level.
Gesehen am 23.06.2020
Keywords: Erde